2008
DOI: 10.1039/b711770a
|View full text |Cite
|
Sign up to set email alerts
|

Microfabricated valveless devices for thermal bioreactions based on diffusion-limited evaporation

Abstract: Microfluidic devices that reduce evaporative loss during thermal bioreactions such as PCR without microvalves have been developed by relying on the principle of diffusion-limited evaporation. Both theoretical and experimental results demonstrate that the sample evaporative loss can be reduced by more than 20 times using long narrow diffusion channels on both sides of the reaction region. In order to further suppress the evaporation, the driving force for liquid evaporation is reduced by two additional techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…However, the possible evaporation-induced liquid loss may result in insufficient PCR product for the detection. To avoid it, integrated chips reported so far have used mineral oils (Anderson et al 2000;Khandurina et al 2000;Lagally et al 2000;Lagally et al 2001;Lee et al 2004;Waters et al 1998), tape (Zhao et al 2003), Bostik's Blu-Tacksilicone (Yeung et al 2008), rubber gaskets (Yoon et al 2002), microvalves (Lagally et al 2001;Lagelly et al 2004;Ramalingam et al 2009), and long narrow diffusion channels (Wang et al 2008). All of them need extra materials to provide physical confinement or extra channel structure.…”
Section: Introductionmentioning
confidence: 99%
“…However, the possible evaporation-induced liquid loss may result in insufficient PCR product for the detection. To avoid it, integrated chips reported so far have used mineral oils (Anderson et al 2000;Khandurina et al 2000;Lagally et al 2000;Lagally et al 2001;Lee et al 2004;Waters et al 1998), tape (Zhao et al 2003), Bostik's Blu-Tacksilicone (Yeung et al 2008), rubber gaskets (Yoon et al 2002), microvalves (Lagally et al 2001;Lagelly et al 2004;Ramalingam et al 2009), and long narrow diffusion channels (Wang et al 2008). All of them need extra materials to provide physical confinement or extra channel structure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lynn et al have shown that the evaporation rate is higher for an expanding reservoir than a contracting reservoir for a given volume of liquid (Lynn et al 2009). Wang et al (2008) also showed that the cross-sectional area of the channel affected the V loss /V ini ratio. In this work, a simple reservoir design consisting of a straight channel with uniform cross-section area is first used to evaluate the effects of different cross-section areas on the V loss /V ini and evaporation rate (Fig.…”
Section: Effect Of Hmdl and Tr's Channel Geometries On The Relative Ementioning
confidence: 92%
“…, the unit vector normal to the interface, the evaporation rate, E, is given by (Berthier et al 2008a). For a three-step PCR thermocycling reaction, Wang et al (2008) have recently proposed a relation expression for the total evaporative volume loss during a DL evaporation process (V loss ) :…”
Section: Principle Of Design For the Hmdl Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Burns et al reported an unsealed reactor for end-point PCR, in which optimized design geometry, thermal isolation and vapor replenishment were employed as methods to reduce evaporative loss (Wang et al 2008). Concerns about PCR failure due to evaporation have been addressed by Burns et al They found that for reactors having bridge channel volumes of less than 10% of the total reaction volume, the overall PCR efficiency in unsealed reactors, was not significantly affected (Wang et al 2008). For our array chip, we controlled evaporative loss of amplification mixture by implementing optimized reactor design geometry, smooth internal reactor surfaces, external heater, selective heating zone, suitable chip substrate based on thermal conductivity and reaction volume.…”
Section: Evaporative Loss Studies In Unsealed Reactorsmentioning
confidence: 99%